Perkembangan Dan Karakteristik Bukti Petunjuk: Dalam Rangka Menyongsong Rancangan Kitab Undang-Undang Hukum Acara Pidana - Nugroho, Fiska Maulidian; Ghufron, Nurul (Acten Journal Law Review, 2025)
he Indonesian Criminal Procedure Code (KUHAP) has established five types of evidence. However, of the five types, there is clue evidence as a type of evidence that belongs to the second degree and is indirect evidence, namely evidence that does not stand alone or indirect evidence that explains a fact in a criminal event. This clue evidence is only owned by the judge and the application of this evidence is authoritative under the subjectivity of a wise judge. The application of clue evidence is guided by Article 188 of the Criminal Procedure Code and if analysed through the characteristics of evidence, there is a problem, namely how clue evidence can be declared as clue evidence when viewed from the characteristics of criminal law evidence. Furthermore, how the Draft Criminal Procedure Code in the future on the validity of evidence of clues that are not reformulated, and replaced with evidence of the judge's own observations. The results of this study found that towards the characteristics of criminal evidentiary law on clue evidence, the evidence should be acceptable, relevant, and legally obtained. However, some incidents of the application of clue evidence show an impression that deviates from the principle of lex certa, namely the principle of clarity, especially in the application by judges. Therefore, there is a need for an evaluative activity towards clue evidence so that it does not become a norm in the Draft Criminal Procedure Code and is more appropriately replaced with evidence of judge's observation. The term judge observation is more appropriate, because this evidence is based on the idea of balance and the purpose of the law of evidence. Throughout this research, this study uses a doctrinal legal research method through a statutory approach and conceptual approach, as well as using a study of the jurisprudence of the Dutch Court and Court Decisions in Indonesia, as well as the doctrines of legal experts. Keywords : Evidence, Clues, Judge's Perception.